Lead paste for high-rate discharge lead-acid storage battery

A lead paste formulation with specific additives enhances mechanical strength and conductivity, addressing the limitations of current lead pastes for high-rate discharge batteries, improving discharge capacity and cycle life.

CN119230820APending Publication Date: 2024-12-31TIANNENG BATTERY GRP (JIANGXI) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411487632.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Current lead pastes for lead-acid batteries fail to meet the requirements of high-current and high-rate discharge, with low utilization rates of active substances and small discharge capacity, leading to reduced cycle life.

Method used

A lead paste formulation for high-rate discharge batteries, comprising positive and negative lead pastes with specific additives such as polyester staple fibers, spherical graphite, precipitated barium sulfate, lignin, and acetylene carbon black, to enhance mechanical strength, conductivity, and adhesion, achieving apparent specific gravities of 4.2-4.3% and 4.4-4.5% respectively.

Benefits of technology

The formulation improves the utilization rate of active materials, discharge capacity, and ensures floating charge use and cycle life, meeting the demands of high-rate discharge applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230820A_ABST
    Figure CN119230820A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lead-acid storage battery pole plate manufacturing, and discloses a high-rate discharge lead-acid storage battery lead paste which is prepared by a battery lead paste preparation process and comprises positive lead paste and negative lead paste in percentage by mass, the positive lead paste comprises lead powder with the oxidation degree of 75-82%, pure water with the mass being 8-11% of that of the lead powder, acid liquor with the mass being 11-11.5% of that of the lead powder and an additive with the mass being 0.18-0.45% of that of the lead powder; except for basic lead powder, pure water and acid liquor, polyester staple fibers and spherical graphite with different mass ratios are added into positive lead paste, polyester staple fibers, precipitated barium sulphate, lignin, humic acid and acetylene black with different mass ratios are added into negative lead paste, so that the apparent specific gravity of the prepared positive lead paste is 4.2-4.3%, the apparent specific gravity of the prepared negative lead paste is 4.4-4.5%, and the apparent specific gravity of the prepared negative lead paste is 4.2-4.3%. The requirements are met, the large-current and high-rate discharge requirements are met, the utilization rate and the discharge capacity of active substances are improved, and the floating charge service life and the cycle service life of the battery are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lead-acid battery plate manufacturing, in particular to a lead paste for a high-rate discharge lead-acid battery. Background Art

[0002] Lead-acid batteries have a history of more than 160 years. As the raw material lead has abundant mineral resources, low price and high battery recycling rate, lead-acid batteries have the advantages of mature technology, no memory effect, high single cell voltage, stable discharge and high safety compared with nickel-metal hydride, nickel-cadmium, lithium and other types of batteries, and lead-acid batteries have the largest market share.

[0003] High-rate (high-power) discharge batteries are mainly used for UPS backup power supplies, and require a higher discharge voltage and a more stable discharge voltage platform to maintain a longer discharge time. Although lithium batteries have a higher voltage than lead-acid batteries, they are inherently unsafe and prone to explosion and fire, and are criticized. They cannot be used in applications with high safety requirements such as central computer rooms and data centers. Most of the application scenarios with high safety requirements use traditional lead-acid batteries.

[0004] The main components of lead-acid batteries are positive plates, negative plates, separators, battery shell covers, electrolytes, positive and negative terminals, and safety valves. The positive and negative plates are the heart of the battery and are the carriers for converting chemical energy into electrical energy. The performance of the plates directly affects the high-rate (high-power) and high-current discharge effect of the battery.

[0005] The main components of the positive plate are the positive grid and positive lead paste, and the main components of the negative plate are the negative grid and negative lead paste. The additives and formulas in the positive and negative lead pastes directly affect the discharge performance and life of the plates. Different formulas are suitable for batteries with different uses. Plates for high-rate (high-power) batteries require lead pastes with strong structure, good conductivity, high porosity, and a high and stable discharge platform.

[0006] After searching, the patent with application number CN201811129702.4 discloses a lead paste for lead-acid batteries, which includes positive lead paste and negative lead paste, and the lead paste components are measured by mass percentage. The positive lead paste adds 0.15-0.3% sodium perborate on the basis of keeping the conventional components unchanged. The negative lead paste adds 0.065-0.08% humic acid on the basis of keeping the conventional components unchanged. Since sodium perborate is added to the positive lead paste, the viscosity and permeability of the paste can be improved, so that the binding force between the grid and the active material is greatly enhanced, and this effect improves the quality of electron transmission. The addition of humic acid to the negative lead paste improves the battery's large current discharge capacity and charge acceptance capacity, and significantly expands the capacity of the lead-acid battery. The above-mentioned performance improvements are conducive to improving the cycle life of lead-acid batteries. The invention increases the cycle life by about 30% compared with the same specification products of the prior art.

[0007] The current lead paste for lead-acid batteries cannot meet the requirements of high-current and high-rate discharge, and the utilization rate of active substances in the lead paste is low and the discharge capacity of the lead paste is small, which reduces the cycle life of the battery. That is, the formula of the current lead paste for lead-acid batteries needs to be optimized to solve the above problems. Therefore, we need to propose a high-rate discharge lead paste for lead-acid batteries. Summary of the invention

[0008] The object of the present invention is to provide a high-rate discharge lead-acid battery lead paste. In addition to basic lead powder, pure water and acid solution, polyester staple fibers and spherical graphite with different mass proportions are added to the positive lead paste, and polyester staple fibers, precipitated barium sulfate, lignin, humic acid and acetylene carbon black with different mass proportions are added to the negative lead paste, so that the apparent specific gravity of the prepared positive lead paste is 4.2-4.3%, and the apparent specific gravity of the prepared negative lead paste is 4.4-4.5%, both of which meet the requirements, meet the requirements of large current and high-rate discharge, improve the utilization rate of active materials and the discharge capacity, and ensure the floating charge use and cycle life of the battery, so as to solve the problems raised in the above-mentioned background technology.

[0009] To achieve the above object, the present invention provides the following technical solution: a lead paste for a high-rate discharge lead-acid battery, prepared by a battery lead paste configuration process, comprising a positive lead paste and a negative lead paste, wherein the positive lead paste comprises, by mass percentage, lead powder with an oxidation degree of 75-82%, pure water with a mass of 8-11% of the mass of the lead powder, acid solution with a mass of 11-11.5% of the mass of the lead powder, and an additive with a mass of 0.18-0.45% of the mass of the lead powder;

[0010] The negative lead paste comprises lead powder with an oxidation degree of 75-82%, pure water with a mass of 7-10% of the mass of the lead powder, acid solution with a mass of 10-10.5% of the mass of the lead powder, and additives with a mass of 1.58-2.75% of the mass of the lead powder;

[0011] The additives in the positive lead paste include:

[0012] Polyester staple fibers used to enhance the mechanical strength of positive lead paste;

[0013] Spherical graphite used to improve the conductivity of positive lead paste;

[0014] The additives in the negative lead paste include:

[0015] Polyester staple fibers used to enhance the mechanical strength of negative lead paste;

[0016] Precipitated barium sulfate for regulating the expansion and contraction of negative lead paste;

[0017] Lignin used to improve the adhesion and plasticity of negative lead paste;

[0018] Corrosive acid used to increase the capacity of the negative plate and improve the charge acceptance of the negative plate;

[0019] Acetylene carbon black used to improve the conductivity of negative lead paste and the discharge capacity of batteries.

[0020] Preferably, the mass of the polyester staple fibers in the positive lead paste additive is 0.08-0.15% of the mass of the lead powder, and the mass of the spherical graphite in the positive lead paste additive is 0.1-0.3% of the mass of the lead powder.

[0021] Preferably, the mass of polyester staple fiber in the negative lead paste additive is 0.08-0.15% of the mass of lead powder, the mass of precipitated barium sulfate in the negative lead paste additive is 1-1.5% of the mass of lead powder, the mass of lignin in the negative lead paste additive is 0.1-0.2% of the mass of lead powder, the mass of corrosive acid in the negative lead paste additive is 0.3-0.6% of the mass of lead powder, and the mass of acetylene black in the negative lead paste additive is 0.1-0.3% of the mass of lead powder.

[0022] Preferably, the positive lead paste comprises, by mass percentage, 1000 kg of lead powder, 8% of pure water by mass of the lead powder, 11% of acid by mass of the lead powder, 0.08% of polyester staple fiber by mass of the lead powder, and 0.1% of spherical graphite by mass of the lead powder;

[0023] The negative lead paste includes 1000kg of lead powder, 7% pure water by mass of the lead powder, 10% acid solution by mass of the lead powder, 0.08% polyester staple fiber by mass of the lead powder, 1% precipitated barium sulfate by mass of the lead powder, 0.1% lignin by mass of the lead powder, 0.3% corrosive acid by mass of the lead powder, and 0.1% acetylene black by mass of the lead powder.

[0024] Preferably, the positive lead paste comprises, by mass percentage, 1000 kg of lead powder, 9.5% of pure water by mass of the lead powder, 11.25% of acid by mass of the lead powder, 0.12% of polyester staple fiber by mass of the lead powder, and 0.2% of spherical graphite by mass of the lead powder;

[0025] The negative lead paste includes 1000kg of lead powder, 8.5% of pure water by mass of the lead powder, 10.25% of acid solution by mass of the lead powder, 0.12% of polyester staple fiber by mass of the lead powder, 1.25% of precipitated barium sulfate by mass of the lead powder, 0.15% of lignin by mass of the lead powder, 0.45% of corrosive acid by mass of the lead powder, and 0.2% of acetylene black by mass of the lead powder.

[0026] Preferably, the positive lead paste comprises, by mass percentage, 1000 kg of lead powder, 11% of pure water by mass of the lead powder, 11.5% of acid by mass of the lead powder, 0.15% of polyester staple fiber by mass of the lead powder, and 0.3% of spherical graphite by mass of the lead powder;

[0027] The negative lead paste includes 1000kg of lead powder, 10% pure water by mass of the lead powder, 10.5% acid solution by mass of the lead powder, 0.15% polyester staple fiber by mass of the lead powder, 1.5% precipitated barium sulfate by mass of the lead powder, 0.2% lignin by mass of the lead powder, 0.6% corrosive acid by mass of the lead powder, and 0.3% acetylene black by mass of the lead powder.

[0028] Preferably, the battery lead paste configuration process includes the following process:

[0029] S1. Preparing lead powder: preparing lead powder from lead block by ball milling or gas phase oxidation;

[0030] S2. Preparing positive lead paste: mixing lead powder, polyester staple fiber and spherical graphite together for dry stirring, and then adding pure water and acid solution respectively for wet stirring, and producing a paste after reaching a desired viscosity;

[0031] S3. Preparation of negative lead paste: lead powder, polyester staple fiber, precipitated barium sulfate, lignin, corrosive acid, and acetylene carbon black are mixed together for dry stirring, and then pure water and acid solution are added respectively for wet stirring to produce a paste after reaching a desired viscosity.

[0032] Preferably, in step S1, when the lead powder is prepared by ball milling, a lead block is placed in a ball mill to generate lead dioxide-coated metal lead particles, i.e., lead powder, through friction and oxidation reaction;

[0033] When lead powder is prepared by gas phase oxidation method, lead liquid at a temperature of 450°C and air are introduced into a gas phase oxidation chamber, and the lead liquid is stirred into fine droplets by a high-speed rotating impeller, which is fully contacted with air for oxidation to generate lead dioxide lead powder, and the lead powder is blown into a cyclone settler for cooling and sedimentation to obtain coarse lead powder, which is then filtered to obtain fine lead powder.

[0034] Preferably, in step S2, the preparation of the positive lead paste includes the following process:

[0035] S21, dry mixing: set the paste mixing program on the paste mixing machine, put the lead powder, polyester staple fiber, and spherical graphite into the paste mixing machine, run the paste mixing machine for 4-5 minutes, and perform preliminary mixing of the dry materials;

[0036] S22, adding pure water: after the dry mixing is completed, add pure water into the paste mixing machine, add pure water for 50-70 seconds, and mix with lead powder and additives;

[0037] S23, adding acid: after the wet mixing is completed, add acid to the paste mixing machine, the time of adding acid is controlled to be 15-20min, and further mix with lead powder, additives and pure water;

[0038] S24, wet mixing: After adding pure water and acid solution to the dry material, continue to mix the lead paste in the paste mixer. The wet mixing time is controlled at 4-6 minutes to improve the uniformity and stability of the lead paste.

[0039] Preferably, in step S3, the preparation of negative lead paste includes the following process:

[0040] S31, dry mixing: set the paste mixing program on the paste mixing machine, put lead powder, polyester staple fiber, precipitated barium sulfate, lignin, corrosive acid, acetylene carbon black into the paste mixing machine, run the paste mixing machine for 4-5 minutes, and perform preliminary mixing of dry materials;

[0041] S32, adding pure water: after the dry mixing is completed, add pure water into the paste mixing machine, add pure water for 50-70 seconds, and mix with lead powder and additives;

[0042] S33, adding acid: after the wet mixing is completed, add acid to the paste mixing machine, the time of adding acid is controlled to be 15-20min, and further mix with lead powder, additives and pure water;

[0043] S34, wet mixing: After adding pure water and acid solution to the dry material, continue to mix the lead paste in the paste mixer. The wet mixing time is controlled at 4-6 minutes to improve the uniformity and stability of the lead paste.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] In addition to basic lead powder, pure water and acid solution, the present invention adds polyester staple fibers and spherical graphite in different mass proportions into the positive lead paste, and adds polyester staple fibers, precipitated barium sulfate, lignin, humic acid and acetylene carbon black in different mass proportions into the negative lead paste, so that the apparent specific gravity of the prepared positive lead paste is 4.2-4.3%, and the apparent specific gravity of the prepared negative lead paste is 4.4-4.5%, both of which meet the requirements, meet the requirements of large current and high rate discharge, improve the utilization rate of active materials and discharge capacity, and ensure the floating charge use and cycle service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 A flowchart of the preparation of the lead paste of the present invention;

[0047] Figure 2 It is a flowchart of the preparation of the positive lead paste of the present invention;

[0048] Figure 3 The figure is a flowchart of the preparation of negative lead paste of the present invention. DETAILED DESCRIPTION

[0049] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] See also Figure 1-3 The present invention provides a technical solution: a lead paste for a high-rate discharge lead-acid battery, which is prepared by a battery lead paste configuration process, and includes a positive lead paste and a negative lead paste. The positive lead paste includes, by mass percentage, lead powder with an oxidation degree of 75-82%, pure water with a mass of 8-11% of the mass of the lead powder, acid solution with a mass of 11-11.5% of the mass of the lead powder, and an additive with a mass of 0.18-0.45% of the mass of the lead powder; the lead powder is converted into lead dioxide during the chemical formation process.

[0051] The negative lead paste includes lead powder with an oxidation degree of 75-82%, pure water with a mass of 7-10% of the mass of the lead powder, acid with a mass of 10-10.5% of the mass of the lead powder, and additives with a mass of 1.58-2.75% of the mass of the lead powder; optionally, the acid is dilute sulfuric acid.

[0052] The additives in the positive lead paste include:

[0053] Polyester staple fibers are used to enhance the mechanical strength of positive lead paste; polyester staple fibers can also reduce the shedding and pulverization of active materials during the charge and discharge process, while also helping to improve the conductivity of the plates.

[0054] Spherical graphite is used to improve the conductivity of positive lead paste and promote electrochemical reactions. At the same time, the spherical structure of spherical graphite also helps to increase the surface area of ​​the plate and improve the activity of the electrochemical reaction.

[0055] The additives in the negative lead paste include:

[0056] Polyester staple fibers used to enhance the mechanical strength of negative lead paste;

[0057] Precipitated barium sulfate is used to adjust the expansion and contraction of negative lead paste; precipitated barium sulfate helps maintain the structural stability of the negative plate. At the same time, barium sulfate is isomorphic to lead sulfate crystals, which is conducive to the formation and uniform distribution of lead sulfate crystals.

[0058] Lignin is used to improve the adhesion and plasticity of negative lead paste; it also helps to maintain the stability of active substances.

[0059] A corrosive acid used to increase the capacity of the negative plate and improve the charge acceptance of the negative plate; the corrosive acid can inhibit the formation and deposition of the lead sulfate passivation layer.

[0060] Acetylene carbon black is used to improve the conductivity of negative lead paste and the discharge capacity of batteries. Especially at the end of discharge, a large amount of lead sulfate crystals will be generated on the negative plate, and the conductivity will drop significantly. Acetylene carbon black can effectively improve this problem.

[0061] The positive electrode material of the battery is usually lead dioxide (PbO2). In the preparation process of positive lead paste, the starting material is often lead powder (Pb). When the positive lead paste is mixed with sulfuric acid and undergoes a chemical formation process, a series of chemical reactions will occur. These reactions ultimately lead to the oxidation of lead powder into lead dioxide (PbO2), while sulfuric acid participates in the reaction and generates lead sulfate (PbSO4) and water (H2O).

[0062] The preparation of negative lead paste also uses lead powder as the starting material. When the negative lead paste is mixed with sulfuric acid and assembled into a battery, during the discharge process, the lead at the negative electrode reacts with sulfuric acid to produce lead sulfate (PbSO4) and positively charged hydrogen ions (H + ). This process is the main reaction of the negative electrode when the battery is discharged.

[0063] The mass of the polyester staple fiber in the positive lead paste additive is 0.08-0.15% of the mass of the lead powder, and the mass of the spherical graphite in the positive lead paste additive is 0.1-0.3% of the mass of the lead powder.

[0064] The mass of polyester staple fiber in the negative lead paste additive is 0.08-0.15% of the mass of lead powder, the mass of precipitated barium sulfate in the negative lead paste additive is 1-1.5% of the mass of lead powder, the mass of lignin in the negative lead paste additive is 0.1-0.2% of the mass of lead powder, the mass of corrosive acid in the negative lead paste additive is 0.3-0.6% of the mass of lead powder, and the mass of acetylene black in the negative lead paste additive is 0.1-0.3% of the mass of lead powder.

[0065] The positive lead paste and negative lead paste for high rate (high power) lead-acid batteries have the following formula:

[0066]

[0067]

[0068] Specifically, in this embodiment, the positive lead paste includes, by mass percentage, 1000 kg of lead powder, 8% of pure water by mass of the lead powder, 11% of acid by mass of the lead powder, 0.08% of polyester staple fiber by mass of the lead powder, and 0.1% of spherical graphite by mass of the lead powder;

[0069] The negative lead paste includes 1000kg of lead powder, 7% pure water by mass of the lead powder, 10% acid solution by mass of the lead powder, 0.08% polyester staple fiber by mass of the lead powder, 1% precipitated barium sulfate by mass of the lead powder, 0.1% lignin by mass of the lead powder, 0.3% corrosive acid by mass of the lead powder, and 0.1% acetylene black by mass of the lead powder.

[0070] Before mixing positive lead paste and negative lead paste, various additives are first configured in proportion, added to the paste mixing machine during the mixing process, and the paste mixing program (dry mixing time, acid adding time, water adding time, wet mixing time, etc.) is set on the paste mixing machine to automatically add the required amount of lead powder, acid, and pure water, and automatically mix evenly. After mixing, the apparent specific gravity of the positive and negative lead pastes is measured to meet the required range.

[0071] The battery lead paste configuration process includes the following steps:

[0072] S1. Preparing lead powder: preparing lead block into lead powder by ball milling or gas phase oxidation;

[0073] In step S1, when the lead powder is prepared by ball milling, a lead block is placed in a ball mill to generate lead dioxide-coated metal lead particles, i.e., lead powder, through friction and oxidation reaction;

[0074] The lead powder is then placed in a designated container or powder storage bin and aged for a certain period of time to ensure its stable performance.

[0075] When lead powder is prepared by gas phase oxidation method, lead liquid at a temperature of 450°C and air are introduced into a gas phase oxidation chamber, and the lead liquid is stirred into fine droplets by a high-speed rotating impeller, which is fully contacted with air for oxidation to generate lead dioxide lead powder, and the lead powder is blown into a cyclone settler for cooling and sedimentation to obtain coarse lead powder, which is then filtered to obtain fine lead powder.

[0076] S2. Preparing positive lead paste: mixing lead powder, polyester staple fiber and spherical graphite together for dry stirring, and then adding pure water and acid solution respectively for wet stirring, and producing a paste after reaching a desired viscosity;

[0077] The addition of additives (polyester staple fibers, spherical graphite) can improve the performance of lead paste, such as increasing the binding force between active substances and increasing the cycle life of the battery.

[0078] In step S2, the preparation of the positive lead paste includes the following process:

[0079] S21. Dry mixing: Set the paste mixing program on the paste mixing machine, put the lead powder, polyester staple fiber and spherical graphite into the paste mixing machine, run the paste mixing machine for 4-5 minutes, and perform preliminary mixing of the dry materials; the dry mixing stage is mainly to mix the dry materials evenly.

[0080] S22, adding pure water: after the dry mixing is completed, add pure water into the paste mixing machine, add pure water for 50-70 seconds, and mix with lead powder and additives;

[0081] S23, adding acid: after the wet mixing is completed, add acid to the paste mixing machine, the time of adding acid is controlled to be 15-20min, and further mix with lead powder, additives and pure water;

[0082] S24, wet mixing: After adding pure water and acid solution to the dry material, continue to mix the lead paste in the paste mixer. The wet mixing time is controlled at 4-6 minutes to improve the uniformity and stability of the lead paste.

[0083] The wet mixing stage is to continue mixing after adding pure water and acid solution to fully mix the materials and reach the required viscosity. The temperature needs to be controlled during the mixing process to avoid excessively high or low temperatures that have an adverse effect on the performance of the lead paste. When the temperature of the lead paste reaches a certain level (such as 75°C), the fan needs to be turned on for exhaust cooling. After the mixing is completed, the qualified lead paste is taken out of the paste mixing machine and prepared for the subsequent plate manufacturing process.

[0084] S3. Preparation of negative lead paste: lead powder, polyester staple fiber, precipitated barium sulfate, lignin, corrosive acid, and acetylene carbon black are mixed together for dry stirring, and then pure water and acid solution are added respectively for wet stirring to produce a paste after reaching a desired viscosity.

[0085] In step S3, the preparation of negative lead paste includes the following process:

[0086] S31, dry mixing: set the paste mixing program on the paste mixing machine, put lead powder, polyester staple fiber, precipitated barium sulfate, lignin, corrosive acid, acetylene carbon black into the paste mixing machine, run the paste mixing machine for 4-5 minutes, and perform preliminary mixing of dry materials;

[0087] S32, adding pure water: after the dry mixing is completed, add pure water into the paste mixing machine, add pure water for 50-70 seconds, and mix with lead powder and additives;

[0088] S33, adding acid: after the wet mixing is completed, add acid to the paste mixing machine, the time of adding acid is controlled to be 15-20min, and further mix with the lead powder, additives and pure water;

[0089] Adding acid helps the lead paste solidify and crystallize and improves the performance of the battery.

[0090] S34, wet mixing: After adding pure water and acid solution to the dry material, continue to mix the lead paste in the paste mixer. The wet mixing time is controlled at 4-6 minutes to improve the uniformity and stability of the lead paste.

[0091] The apparent specific gravity of the positive lead paste prepared by the above process is 4.2-4.3%, and the apparent specific gravity of the negative lead paste is 4.4-4.5%.

[0092] Example 2

[0093] The same points as the above embodiment will not be repeated here, except that:

[0094] In terms of percentage by mass, the positive lead paste comprises 1000 kg of lead powder, 9.5% of pure water by mass of the lead powder, 11.25% of acid by mass of the lead powder, 0.12% of polyester staple fiber by mass of the lead powder, and 0.2% of spherical graphite by mass of the lead powder;

[0095] The negative lead paste includes 1000kg of lead powder, 8.5% of pure water by mass of the lead powder, 10.25% of acid solution by mass of the lead powder, 0.12% of polyester staple fiber by mass of the lead powder, 1.25% of precipitated barium sulfate by mass of the lead powder, 0.15% of lignin by mass of the lead powder, 0.45% of corrosive acid by mass of the lead powder, and 0.2% of acetylene black by mass of the lead powder.

[0096] The apparent specific gravity of the positive lead paste prepared by the lead paste formula of this embodiment is 4.15-4.25%, and the apparent specific gravity of the negative lead paste is 4.38-4.48%.

[0097] Example 3

[0098] The same points as the above embodiment will not be repeated here, except that:

[0099] In terms of percentage by mass, the positive lead paste comprises 1000 kg of lead powder, 11% of pure water by mass of the lead powder, 11.5% of acid by mass of the lead powder, 0.15% of polyester staple fiber by mass of the lead powder, and 0.3% of spherical graphite by mass of the lead powder;

[0100] The negative lead paste includes 1000kg of lead powder, 10% pure water by mass of the lead powder, 10.5% acid solution by mass of the lead powder, 0.15% polyester staple fiber by mass of the lead powder, 1.5% precipitated barium sulfate by mass of the lead powder, 0.2% lignin by mass of the lead powder, 0.6% corrosive acid by mass of the lead powder, and 0.3% acetylene black by mass of the lead powder.

[0101] The apparent specific gravity of the positive lead paste prepared by the lead paste formula of this embodiment is 4.26-4.36%, and the apparent specific gravity of the negative lead paste is 4.43-4.54%.

[0102] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high-rate discharge lead-acid battery lead paste, prepared by a battery lead paste configuration process, characterized in that: The positive lead paste comprises a positive lead paste and a negative lead paste. The positive lead paste comprises, by weight percentage, lead powder with an oxidation degree of 75-82%, pure water with a weight of 8-11% of the weight of the lead powder, acid solution with a weight of 11-11.5% of the weight of the lead powder, and additives with a weight of 0.18-0.45% of the weight of the lead powder. The negative lead paste comprises lead powder with an oxidation degree of 75-82%, pure water with a mass of 7-10% of the mass of the lead powder, acid solution with a mass of 10-10.5% of the mass of the lead powder, and additives with a mass of 1.58-2.75% of the mass of the lead powder; The additives in the positive lead paste include: Polyester staple fibers used to enhance the mechanical strength of positive lead paste; Spherical graphite used to improve the conductivity of positive lead paste; The additives in the negative lead paste include: Polyester staple fibers used to enhance the mechanical strength of negative lead paste; Precipitated barium sulfate for regulating the expansion and contraction of negative lead paste; Lignin used to improve the adhesion and plasticity of negative lead paste; Corrosive acid used to increase the capacity of the negative plate and improve the charge acceptance of the negative plate; Acetylene carbon black used to improve the conductivity of negative lead paste and the discharge capacity of batteries.

2. The high-rate discharge lead-acid battery lead paste according to claim 1, characterized in that: The mass of the polyester staple fiber in the positive lead paste additive is 0.08-0.15% of the mass of the lead powder, and the mass of the spherical graphite in the positive lead paste additive is 0.1-0.3% of the mass of the lead powder.

3. The high-rate discharge lead-acid battery lead paste according to claim 1, characterized in that: The mass of polyester staple fiber in the negative lead paste additive is 0.08-0.15% of the mass of lead powder, the mass of precipitated barium sulfate in the negative lead paste additive is 1-1.5% of the mass of lead powder, the mass of lignin in the negative lead paste additive is 0.1-0.2% of the mass of lead powder, the mass of corrosive acid in the negative lead paste additive is 0.3-0.6% of the mass of lead powder, and the mass of acetylene black in the negative lead paste additive is 0.1-0.3% of the mass of lead powder.

4. The high-rate discharge lead-acid battery lead paste according to claim 1, characterized in that: In terms of percentage by mass, the positive lead paste comprises 1000 kg of lead powder, 8% of pure water by mass of the lead powder, 11% of acid by mass of the lead powder, 0.08% of polyester staple fiber by mass of the lead powder, and 0.1% of spherical graphite by mass of the lead powder; The negative lead paste includes 1000kg of lead powder, 7% pure water by mass of the lead powder, 10% acid solution by mass of the lead powder, 0.08% polyester staple fiber by mass of the lead powder, 1% precipitated barium sulfate by mass of the lead powder, 0.1% lignin by mass of the lead powder, 0.3% corrosive acid by mass of the lead powder, and 0.1% acetylene black by mass of the lead powder.

5. The high-rate discharge lead-acid battery lead paste according to claim 1, characterized in that: In terms of percentage by mass, the positive lead paste comprises 1000 kg of lead powder, 9.5% of pure water by mass of the lead powder, 11.25% of acid by mass of the lead powder, 0.12% of polyester staple fiber by mass of the lead powder, and 0.2% of spherical graphite by mass of the lead powder; The negative lead paste includes 1000kg of lead powder, 8.5% of pure water by mass of the lead powder, 10.25% of acid solution by mass of the lead powder, 0.12% of polyester staple fiber by mass of the lead powder, 1.25% of precipitated barium sulfate by mass of the lead powder, 0.15% of lignin by mass of the lead powder, 0.45% of corrosive acid by mass of the lead powder, and 0.2% of acetylene black by mass of the lead powder.

6. The high-rate discharge lead-acid battery lead paste according to claim 1, characterized in that: In terms of percentage by mass, the positive lead paste comprises 1000 kg of lead powder, 11% of pure water by mass of the lead powder, 11.5% of acid by mass of the lead powder, 0.15% of polyester staple fiber by mass of the lead powder, and 0.3% of spherical graphite by mass of the lead powder; The negative lead paste includes 1000kg of lead powder, 10% pure water by mass of the lead powder, 10.5% acid solution by mass of the lead powder, 0.15% polyester staple fiber by mass of the lead powder, 1.5% precipitated barium sulfate by mass of the lead powder, 0.2% lignin by mass of the lead powder, 0.6% corrosive acid by mass of the lead powder, and 0.3% acetylene black by mass of the lead powder.

7. The high-rate discharge lead-acid battery lead paste according to claim 1, characterized in that: The battery lead paste configuration process includes the following steps: S1. Preparing lead powder: preparing lead block into lead powder by ball milling or gas phase oxidation; S2. Preparing positive lead paste: mixing lead powder, polyester staple fiber and spherical graphite together for dry stirring, and then adding pure water and acid solution respectively for wet stirring, and producing a paste after reaching a desired viscosity; S3. Preparation of negative lead paste: lead powder, polyester staple fiber, precipitated barium sulfate, lignin, corrosive acid, and acetylene carbon black are mixed together for dry stirring, and then pure water and acid solution are added respectively for wet stirring to produce a paste after reaching a desired viscosity.

8. The high-rate discharge lead-acid battery lead paste according to claim 7, characterized in that: In step S1, when the lead powder is prepared by ball milling, a lead block is placed in a ball mill to generate lead dioxide-coated metal lead particles, i.e., lead powder, through friction and oxidation reaction; When lead powder is prepared by gas phase oxidation method, lead liquid at a temperature of 450°C and air are introduced into a gas phase oxidation chamber, and the lead liquid is stirred into fine droplets by a high-speed rotating impeller, which is fully contacted with air for oxidation to generate lead dioxide lead powder, and the lead powder is blown into a cyclone settler for cooling and sedimentation to obtain coarse lead powder, which is then filtered to obtain fine lead powder.

9. The high-rate discharge lead-acid battery lead paste according to claim 7, characterized in that: In step S2, the preparation of the positive lead paste includes the following process: S21, dry mixing: set the paste mixing program on the paste mixing machine, put the lead powder, polyester staple fiber, and spherical graphite into the paste mixing machine, run the paste mixing machine for 4-5 minutes, and perform preliminary mixing of the dry materials; S22, adding pure water: after the dry mixing is completed, add pure water into the paste mixing machine, add pure water for 50-70 seconds, and mix with lead powder and additives; S23, adding acid: after the wet mixing is completed, add acid to the paste mixing machine, the time of adding acid is controlled to be 15-20min, and further mix with the lead powder, additives and pure water; S24, wet mixing: After adding pure water and acid solution to the dry material, continue to mix the lead paste in the paste mixer. The wet mixing time is controlled at 4-6 minutes to improve the uniformity and stability of the lead paste.

10. The lead paste for high-rate discharge lead-acid batteries according to claim 7, characterized in that: In step S3, the preparation of negative lead paste includes the following process: S31, dry mixing: set the paste mixing program on the paste mixing machine, put lead powder, polyester staple fiber, precipitated barium sulfate, lignin, corrosive acid, acetylene carbon black into the paste mixing machine, run the paste mixing machine for 4-5 minutes, and perform preliminary mixing of dry materials; S32, adding pure water: after the dry mixing is completed, add pure water into the paste mixing machine, add pure water for 50-70 seconds, and mix with lead powder and additives; S33, adding acid: after the wet mixing is completed, add acid to the paste mixing machine, the time of adding acid is controlled to be 15-20min, and further mix with lead powder, additives and pure water; S34, wet mixing: After adding pure water and acid solution to the dry material, continue to mix the lead paste in the paste mixer. The wet mixing time is controlled at 4-6 minutes to improve the uniformity and stability of the lead paste.

Citation Information

Patent Citations

  • Lead plaster of lead-acid storage battery

    CN109301208A